2020
DOI: 10.21203/rs.2.22515/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Patient satisfaction and quality of life in breast reconstruction: assessment of outcomes of immediate, delayed, and nonreconstruction.

Abstract: Objectives This study was conducted aiming to assess the quality of life and satisfaction of women who had mastectomy treated with and without breast reconstruction. Results A total of 81 women who had mastectomy were included, of whom 53 (65.4%) underwent breast reconstruction. Quality of life was not significantly better in the reconstruction group than the nonreconstruction group. Satisfaction with the surgically operated breast, whether reconstructed or not, was positively correlated with quality of lif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that breast reconstruction can help to maintain the aesthetic appearance of the body, which can help to rebuild the patient's self-confidence, reduce their psychological trauma, and improve their quality of life (4,5). However, a number of studies have reported that the life quality of women who undergo breast reconstruction after surgery is not higher than that of women who undergo pure breast resection (6).…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that breast reconstruction can help to maintain the aesthetic appearance of the body, which can help to rebuild the patient's self-confidence, reduce their psychological trauma, and improve their quality of life (4,5). However, a number of studies have reported that the life quality of women who undergo breast reconstruction after surgery is not higher than that of women who undergo pure breast resection (6).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, a study in Brazil showed that quality of life was not significantly better in the reconstruction group than in the non-reconstruction group, and there was no significant difference in the quality of life between women with immediate and delayed reconstruction. That study showed that the satisfaction of patients with the operated breast, reconstructed or not, is more important in the quality of life than whether the breast was reconstructed or not [38]. Dauplat et al (2017), found that mastectomy followed by reconstruction preserved the QOL, but only if reconstruction was for certain types of patients, such as young age [39].…”
Section: Discussionmentioning
confidence: 99%
“…Breast reconstruction constitutes the basic principle in the present-day surgical treatment of breast cancer [45,46]. Approximately 60% of the participants would recommend total immediate breast reconstruction, with the most commonly suggested technique being definitive implants followed by tissue expanders.…”
Section: Discussionmentioning
confidence: 99%